Alarm management practices in natural gas processing plants. (October 2016) - Soares, Vinícius Barroso; Pinto, José Carlos; de Souza, Maurício Bezerra
Abstract: In industrial data sets, groups of variables often move together. Monitoring all these variables may result in many nuisance alarms. However, it is possible to take advantage of redundant information to design and reduce the size of alarm sets. The present work reports the application of an alarm management protocol based on alarm priorization to three large Natural Gas Processing Plants, during a three year period, and also investigates the use of different correlation analyses techniques as tools to assist in the further reduction of the number of alarms. The results show that the adopted practices enable the reduction of alarms. Highlights: The application of alarm management reduced in 74% the alarm activation ratio. Correlation between variables may change due to different conditions. The correlation patterns exhibited during the faults may be used to diagnose them. When grouping PC alarms, physical alarms should be kept visible in a second screen.